Defect in signal transduction at the level of the plasma membrane accounts for inability of insulin to activate pyruvate dehydrogenase in white adipocytes of lactating rats. - Kilgour, E (1988)
1. The mechanism responsible for the failure of insulin to activate pyruvate dehydrogenase (PDH) in white adipose tissue in vivo during lactation was investigated. 2. Insulin failed to increase PDH in isolated adipocytes from lactating rats. 3. Insulin binding to plasma membranes from adipocytes was unchanged by lactation. 4. Incubation of plasma membranes plus permeabilized mitochondria from adipocytes in the presence of insulin resulted in activation of PDH when the plasma membranes were obtained from virgin rats, whereas no activation was observed when plasma membranes from lactating rats were used. 5. The results show that the failure of insulin to activate PDH in adipose tissue from lactating rats is due to a failure of the signal-transduction system in the plasma membrane at steps subsequent to insulin binding to the insulin receptor.